Effect of Various Levels of Bitter Melon (Momordica Charanta, L) Leaf Juice on the Growth of Broiler Chicks - Horhoruw, Wiesje Martha (Journal of Comprehensive Science, 2025)
Bitter melon (Momordica charantia) leaves, which are rich in nutrients and bioactives (flavonoids, folacin), have potential as a natural feed additive to improve broiler growth, but research on their use in drinking water is limited. This study aimed to determine the effect of various levels of bitter melon leaf juice in drinking water on broiler growth performance. This study used a completely randomized design with 4 treatments (0 ml, 10 ml, 12.5 ml, 15 ml/day) and 20 replicates. Variables measured included feed consumption, body weight, FCR, and drinking water consumption for 6 weeks. Data were analyzed by ANOVA and Duncan's test. The 12.5 ml/day treatment resulted in the highest body weight gain (1746.55 g) and the best feed consumption (3140.05 g), significantly different (P<0.05) from the control and the 15 ml dose. However, FCR was not significantly different (1.81 vs. 1.79 control), indicating increased growth without improved feed efficiency. Bitter melon leaf juice 12.5 ml/day is effective as a natural growth stimulant, but needs to be combined with other ingredients for FCR optimization. Further research is recommended to explore the bioactive mechanism, economic test, and commercial scale application.